Secure node ID assignment for internet integrated sensor network. Issue 2 (22nd June 2022) - Gautam, Amit Kumar; Kumar, Rakesh
Internet integrating sensor network (IISN) has gained much importance and exponential growth has been seen over the last 20 years. It is typically installed in remote and unattended terrains to monitor, process and collect time-critical and sensitive data. Internet integrated wireless sensor network can be used in various critical sectors such as monitoring of nuclear power plant, disaster management, internet of things (IoT), industrial management etc. As the application area of sensor network is increasing rapidly, the adversaries can trigger duplicate ID based attacks such as Clone and Sybil attacks. In this paper, for joining a new node in the existing network, we propose a secure identity assignment who wishes to join the network with the help of any existing node of the network. With the collaboration of an existing node, an overlay ID will be assigned to new node which is secured by using a public key cryptography. The paper included a complexity and communication overhead analysis to demonstrate the effectiveness of proposed method which maximises the defence/protection against ID based attacks. Complexity analysis demonstrates the superiority of the proposed method. The proposed approach takes 33.33% less message transfer and approximate 70% less computation cost than compared approach.